The reality of using distributed leadership in distance education in public schools in Al-Kharj - Al-Qahtani, Asmaa Ahmed; Al-Saqer, Abdulaziz Mohammed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the current status of distributed leadership in remote education in Al-Kharj public schools, identify the obstacles of practicing distributed leadership in remote education, and determine the requirements for improving distributed leadership practices from the perspectives of school principals and vice principals. Additionally, the study aimed to examine the statistical significance of differences between the mean of distributed leadership based on age group (primary, secondary, and high school) and job title (principal or vice principal). The study used a descriptive survey method, with a study population consisting of 195 principals and 171 vice principals. The study sample consisted of 135 principals and 117 vice principals. The study used a questionnaire as a tool for the study. The study reached a number of results, including the following: the study sample strongly agreed (with a mean score of 4.06) on the application of distributed leadership in remote education in Al-Kharj public schools. The sample also expressed low agreement (with a mean score of 2.49) on the obstacles of practicing distributed leadership in remote education, while showing high agreement (with a mean score of 3.82) on the requirements for improving distributed leadership practices. The results indicated no statistically significant differences at the 0.05 level or less in the responses of the study sample regarding the first domain (vision, mission, and goals) and the second domain (shared responsibility) based on job title. However, statistically significant differences were found in the responses regarding the fifth domain (teacher leaders) and the third domain (organizational culture) and fourth domain (leadership practices) based on job title, favoring school principals. Furthermore, the results showed no statistically significant differences in all domains of distributed leadership practices in remote education in Al-Kharj public schools based on age group.
Keywords: Distributed leadership; Remote education